Features of natural population movement in the Siberian Federal District during the coronavirus pandemic - M. I. Voevoda; V. M. Chernyshev; I. F. Mingazov (Сибирский научный медицинский журнал, 2023)
The pandemic of a new corona virus infection (NCVI) has worsened the already unfavorable demographic situation in the Russian Federation. Aim of the study was to assess the changes in the demographic situation in the country and the Siberian Federal District and the causes contributing to them. Material and methods. Statistical data of the Ministry of Health of the Russian Federation, Rosstat, regional ministries of health of subjects belonging to the Siberian Federal District, and literature on the problems of demography were used. The following methods were used: analytical, historical, statistical, including statistical observation, summary and grouping of materials, absolute and relative statistical values, sampling. Results and discussion. The pandemic period of the new coronavirus infection in RF and SFD is characterized by a substantial increase in the mortality rate, which became the maximum in the newest history of Russia, i.e. since 1991. The structure of the main causes of death has changed. Diseases of the circulatory system, neoplasms, diseases of the digestive organs and external causes, accounted for 76.6 % of all causes in 2019, in 2021 they accounted for only 60.1 %, with NCVI taking second place among causes of death (19.1 %). The birth rate remains at a low level, and in 2021 was 9.6 per 1000 population, which is 16.5 % lower than in 2017, due to which the natural decline in population has significantly increased (to –6.3 in Russia and to –7.0 per 1000 population in SFD) and the average life expectancy has decreased. Conclusions. All of the foregoing points to the ineffectiveness of measures to prevent and forestall the adverse effects of the pandemic, which is practically inevitable in the case of new, poorly studied infectious diseases. The measures taken to organize medical care to the population in the conditions of the pandemic have not been adequate. This is evidenced by the higher rates of total mortality of the population, compared to the probable ones (caused by the increase in mortality from NCVI), a significant increase in natural population decline and a reduction in life expectancy.